Cytotoxic function of xylanase VdXyn4 in the plant vascular wilt pathogen Verticillium dahliae. Issue 1 (15th June 2021) - Wang, Dan; Chen, Jie-Yin; Song, Jian; Li, Jun-Jiao; Klosterman, Steven J.; Li, Ran; Kong, Zhi-Qiang; Subbarao, Krishna V.; Dai, Xiao-Feng; Zhang, Dan-Dan
Abstract: Phytopathogen xylanases play critical roles in pathogenesis, likely due to their ability to degrade plant structural barriers and manipulate host immunity. As an invader of plant xylem vessels, the fungus Verticillium dahliae is thought to deploy complex cell wall degrading enzymes. Comparative genomics analyses revealed that the V. dahliae genome encodes a family of six xylanases, each possessing a glycosyl hydrolase 11 domain, but the functions of these enzymes are undetermined. Characterizing gene deletion mutants revealed that only V. dahliae xylanase 4 (VdXyn4) degraded the plant cell wall and contributed to the virulence of V. dahliae . VdXyn4 displayed cytotoxic activity and induced a necrosis phenotype during the late stages of infection, leading to vein and petiole collapse that depended on the enzyme simultaneously localizing to nuclei and chloroplasts. The internalization of VdXyn4 was in conjunction with that of the plasma membrane complexLeucine-rich repeat (LRR)-receptor-like kinase suppressor of BIR1-1 (SOBIR1)/LRR-RLK BRI1-associated kinase-1 (BAK1), but we could not rule out the possibility that VdXyn4 may also act as an apoplastic effector. Immune signaling (in the SA–JA pathways) induced by VdXyn4 relative to that induced by known immunity effectors was substantially delayed. While cytotoxic activity could be partially suppressed by known effectors, they failed to impede necrosis in Nicotiana benthamiana . Thus, unlike typical effectors, cytotoxicity of VdXyn4 plays a crucial intracellular role at the late stages of V. dahliae infection and colonization, especially following pathogen entry into the xylem; this cytotoxic activity is likely conserved in the corresponding enzyme families in plant vascular pathogens. Abstract : By virtue of its cytotoxic activity, Verticillium dahliae Xylanase induces necrosis, leading to vein and petiole collapse that depends on the enzyme simultaneously localizing to nuclei and chloroplasts.